RESPONSE OF SOME CHARACTERISTICS OF WHEAT GROWTH TO SPRAYING WITH VITAMIN B9 AND E - H. A. Baqir; N. H. Zeboon (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Over the course of two winter periods, researchers at the Agricultural Experiment Unit, College of Agricultural Engineering Sciences, University of Baghdad, studied the effects of covering wheat (the Al-Furat variety) and “vitamins B9” (“folic acid”) and E “(tocopherol)” on a number of growth traits. Three independent trials were conducted utilizing a factorial design within a Randomized Complete Block Design. The first component was folic acid at 0, 250, and 500 mg L-1; the second component was vitamin E at 0, 1, and 2 ml L-1. At the start of the tillering and flowering stages, both vitamins were applied. All measured characteristics (plant height, flag leaf area, total tiller count, plant dry weight at booting and 100% blooming phases, and “vitamin B9” 500 mg L-1) were found exceeded at this dosage. Aside from that, total chlorophyll, chlorophyll a and b content in leaves, and the pace of crop growth.Since the focus of 2 ml L-1 was higher than most of the attributes, applying vitamin E influenced the growth characteristics. The number of tillers, plant dry weight, crop growth rate, total chlorophyll, biological yield, chlorophyll a and b in leaves.